Counseling people living in poverty: The CARE model - Foss, L.L.; Generali, M.M.; Kress, V.E. (Journal of Humanistic Counseling, 2011)
Counselors frequently counsel clients who live in poverty. The authors describe the new CARE model that addresses the influence of multiple systems on poor clients' experiences. A social justice, humanistic intervention, the CARE model emphasizes cultivating a positive counseling relationship with poor clients, empathizing with their unique realities, and working to remove barriers to future success and well-being by building on their strengths. © 2011 by the American Counseling Association.
Keywords: dept.csp

The church, the closet, and the couch: the counselor's role in assisting clients to integrate their sexual orientation and religious identity - Ginicola, Misty M; Smith, Cheri (Journal of Lgbt Issues in Counseling, 2011)
In a recent article in The New York Times, therapy using Sexual Orientation Management was highlighted, with the focus on therapists assisting clients to live a heterosexual life because of their religious beliefs.The primary reasons for such an approach are to allow for client choice and respect on an equally important area of diversity, their religious affiliation and values.Although research has been performed on the intersection of religion and sexual orientation, there has not been an extensive analysis or criticism of this management technique.In this article, the authors explore the experience of religious clients struggling with their sexual orientation, discuss the potential counselor responses to sexual orientation religious issues, and the impact of each on the counseling field using ethical principles, existing research, and logical outcomes.© 2011 Copyright Taylor and Francis Group, LLC.
Keywords: LGBQ; counseling; dept.csp; ethics; religion